Surgical treatment of penetrating atherosclerotic ulcer of the descending aorta - Kovačević, Pavle; Velicki, Lazar; Popović, Dušan; Ivanović, Vladimir; Mojašević, Renata (Vojnosanitetski pregled, 2013)
Introduction. The term “penetrating atherosclerotic ulcer” (PAU) of the aorta describes the condition in which ulceration of an aortic atherosclerotic lesion penetrates the internal elastic lamina into media. PAU is a high-risk lesion due to its deleterious effects on the integrity of aortic wall, with potentially fatal outcome. Case report. A patient with intensive, sharp chest pain irradiating to the back but with no signs of myocardial ischemia on an electrocardiogram was referred to our hospital. Transthoracic echocardiography showed no pathological changes of the ascending aorta. However, multislice computed tomography (CT) showed an aortic ulcer with varying degree of the subadventitial hemorrhage in the region of the thoracic aorta at the level of Th 8–9. Due to imminent rupture of the penetrating aortic ulcer, the patient was promptly prepared for surgery. A 15 cm long subadventitial hematoma was found intraoperatively in the right posterolateral aspect of the descending aorta, 5 cm above the diaphragm and 7 cm below the origin of the left subclavial artery. The affected segment of the aorta was resected, followed by an inlay aortic reconstruction with a Dacron tube graft of 24 mm. Control CT revealed satisfactory reconstruction of the descending aorta. Conclusion. PAU is a rare, but potentially fatal disease. Open surgery in patients with PAU is an effective treatment strategy, although endovascular treatment options are emerging. Key words:aorta, thoracic; aortic rupture; atherosclerosis; ulcer; diagnostic techniques and procedures; cardiovascular surgical procedures; transplants.
Keywords: aortic diseases; surgery; Ulcer; Penetrance; Aorta